Hubungan Prestasi Belajar Tilawah Dan Tahfidz Al-Quran (TTQ) Dengan Prestasi Belajar Pendidikan Agama Islam (Studi Deskriptif di SMA IT Fithrah Insani Kec. Ngamprah Kab. Bandung Barat) - Ilyas Rifa'i; Neng Ayu Sulastri (STAI Siliwangi Bandung, 2017)
Quran recitations are reciting the verses of the Qur'an well and correctly. While tahfidz al-Quran is the process of studying the Koran by memorizing the verses of the Koran. Islamic Religious Education (PAI) as one of the subjects that students studied in high school has a fairly fundamental role in the formation of personality. Among the material he taught is usually the exposure of theories and arguments of the Qur'an or hadith that must be remembered and understood by the students. This certainly requires good concentration and memory of the students while learning it.Therefore, the better the students' ability to read and memorize the Koran, the better will be their ability in knowing the various propositions that have to do with the material of the PAI that is studied.This study aims to determine the achievement of learning TTQ, PAI learning achievement, and the relationship of learning achievement with TTQPAI student achievement in high school IT Fithrah Insani. PAI play a very important role in improving the personality and build a whole human devoted to God Almighty. Efforts to improve the quality and achievement of learning PAI, have a connection with certain subjects that support. In connection with the improvement of PAI learning achievement, the subjects of PAI relate to TTQ subjects. This research uses descriptive correlational research method with quantitative approach. The results of research as follows: First, the achievement of learning TTQ students’ year 2017/2018 class semester odd is quite good, where students have an average on the lesson (variable X) is 87.11. Second, the achievement of PAI learning in the 2017/2018 semester class is anodd semester, where the average student in the lesson (variable Y) is 83.61. Third, there is arelationship between learning achievement of TTQ with learning achievement of PAI equal to 0,815, mean correlation is positive. This means that correlation between learning achievement of TTQ with learning achievement of PAI equal to 66,42%. Based on theresearch result, it can be concluded that research hypothesis has arelationship which is significant to the learning achievement of TTQ and PAI learning achievement in SMA IT Fithrah Insani.